The Impact of Artificial Intelligence, Ethical Implications and Technologies on the Electoral Process - Itumeleng Michael Maine; Bukohwo Michael Esiefarienrhe (E-Journal of Humanities, Arts and Social Sciences)
The benefits in the use of Artificial Intelligence (AI) in the electoral process are enormous only when AI is used ethically and all stakeholders particularly those vested with the responsibility to conduct elections are ethically upright in their use of AI. The problem this paper seeks to address is how AI can be ethically used to aid the smooth conduct of elections and how can the benefits of AI be harnessed in the electioneering process. The methodology used in both data collection and analysis was expert judgement and systematic review. This paper analysed the various AI tools and techniques that are used to assist in the conduct of credible elections. Also discussed are the various ways that AI can be used negatively to influence voters namely deepfakes, automated bots, data privacy breaches, microtargeting, psychological profiles of voters, voting pattern prediction, and cyberattacks of electronic devices with the intention to rig elections. It is recommended that the ethical use of AI in elections should be advocated, and training of the citizens on the role of AI before, during and after elections and how to handle AI-related threats should be conducted well ahead of elections.